ASSESING THE EFFECTIVENESS OF TREATMENT FOR MIGRAINE PATIENTS USING THE MIGREN PRO MOBILE APPLICATION - Farrukh S. Saidvaliyev; Aziza Kh. Subkhanova (Central Asian Journal of Medicine, 2023)
The article illustrates evaluating the effectiveness of treatment in patients using a mobile application in the treatment and controlling yhe migraine. The aim of the study is to improve migtaine behavioral skills and knowledge in patients who use the mobile application, to control medication intake, and to achieve the effectiveness of treatment without other additional drugs by monitoring the elimination of migraine triggers on a daily basis. During the research, 88 (100%) patients were observed. The patients were divided into two groups, the patients of the first group were recommended daily monitoring of migraine in paper form, and the patients of the second group were recommended the "MIGREN PRO" mobile application. All patients were re-examined after 3 months. In patients who used the mobile application, the number and duration of headache decreased, cognitive functions were restored, the level of depression decreased, and the quality of life improved.